2020
DOI: 10.1002/emp2.12229
|View full text |Cite
|
Sign up to set email alerts
|

Lack of benefit from hospitalization in patients with syncope: A propensity analysis

Abstract: Study Objective Patients with syncope are frequently admitted to the hospital, but whether this improves outcome is unknown. We tested whether hospitalization reduced mortality in patients who presented to emergency departments (EDs) with syncope. Methods We conducted a propensity analysis of the outcomes of patients ≥18 years old presenting to EDs with a primary diagnosis of syncope in April 2004–March 2013. The model used 1:1 nearest‐neighbor matching to predicted adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
5
0
3
Order By: Relevance
“…It is well known that lack of adherence to guidelines increases admission rates and costs [26] without additional useful information [23]. Hospitalization in patients with syncope does not reduce early or late mortality [27]. According to Krishnan et al, the benefit of hospital admission is low for patients at low risk of serious adverse events [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that lack of adherence to guidelines increases admission rates and costs [26] without additional useful information [23]. Hospitalization in patients with syncope does not reduce early or late mortality [27]. According to Krishnan et al, the benefit of hospital admission is low for patients at low risk of serious adverse events [28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, knowing the type and timing of short-term adverse events is essential for deciding how long and in which setting we should observe patients [7]. Knowledge of short and medium-term outcomes might aid decision making with respect to hospital admission and syncope units [8][9][10]. Previous attempts have been made to describe the incidence of adverse events after syncope by using meta-analyses [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, knowing the type and timing of short-term adverse events is essential in order to decide how long and in which setting we should observe patients [7]. Furthermore, it might aid decision making with respect to hospital admission and syncope units [8][9][10]. Moreover, assessing long-term outcomes after syncope might better inform differences between short and long-term risk factors and the possible role of different approaches (e.g., hospital admission and proper follow-up) for improving patients' outcomes [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Probst et al found no significant difference after 30 days in serious events in syncope patients more than 60 years old with no serious ED diagnosis in American patients who are admitted to hospital when compared to the discharged group (propensity analysis) [ 60 ]. In a province-wide analysis from Alberta, Canada, hospitalized syncope patients had higher 30-day (3.6% vs. 0.3%) and one-year (14.3% vs. 3.0%) mortality rates when compared to discharged patients [ 11 ]. Upon discharge, 43% of the patients were discharged with a primary diagnosis of syncope, while the rest were discharged with an alternate diagnosis.…”
Section: The Role Of Hospitalization and Outpatient Referralmentioning
confidence: 99%
“…Of note, almost half of admitted patients in this study were older than 65 years and had significant cardiac comorbidities. In a propensity score analysis of 8864 patients admitted from the ED within 48 h, Kaul et al found that admitted patients were significantly older, lived in rural areas, were mostly males, and had lower income [ 11 ]. Neither short- nor long-term mortality was reduced in hospitalized patients compared to a matched cohort.…”
Section: Introductionmentioning
confidence: 99%